Efficient Identity-Based Universal Designated Verifier Signature Proof Systems - Yifan Yang; Xiaotong Zhou; Binting Su; Wei Wu (Mathematics)
The implementation of universal designated verifier signatures proofs (UDVSPs) enhances data privacy and security in various digital communication systems. However, practical applications of UDVSP face challenges such as high computational overhead, onerous certificate management, and complex public key initialization. These issues hinder UDVSP adoption in daily life. To address these limitations, existing solutions attempt to eliminate bilinear pairing operations, but their proposal still involves cumbersome certificate management and inherent interactive operations that can sometimes significantly degrade system efficiency. In this paper, we first utilize the identity-based (ID-based) SM2 digital signature scheme to construct an ID-based UDVSP system which sidesteps the cumbersome certificate management issue. To further remove the interactive requirement, we also employ the OR proof and Fiat–Shamir technologies to design the other ID-based UDVSP system. Our designs not only possess the same bilinear pairing-free advantage as Lin et al.’s proposal, but also achieve the certificate-free or non-interactive goals. Security proofs and performance analysis confirm the viability and efficiency of our systems.